PP01.2 – 2772: Whole exome sequencing in 41 cases of early-onset epileptic encephalopathy - Macaya, A.; Marcé-Grau, A.; Cuenca-León, E.; Felipe-Rucián, A.; López-Pisón, F.J.; Raspall-Chaure, M. (European journal of paediatric neurology, 2015)
To use whole exome sequencing (WES) to investigate the genetic cause in a cohort of infants with early-onset epileptic encephalopathy (EOEE). Subjects: 41 trios from tertiary hospital setting. All probands were unrelated, had severe neurodevelopmental disorders and seizure onset within first year of life. Studies included brain MRI, extensive metabolic screen and aCGH. Exome capture and enrichment was performed using NimbleGen SeqCap EZ Exome v3.0 and Illumina TruSeq kits. Libraries were sequenced at 30X coverage in a HiSeq 2000 instrument. The 123 exomes were aligned to NCBI build 37 RefSeq. Variants were jointly called with GATK Haplotype Caller, annotated using SnpEff and VarAnnot and classified according to predicted functional effect. Analysis was two-tiered and comprised evaluation of 169 epilepsy-related genes, followed by evaluation of other functional candidates. All pathogenic variants were validated by Sanger sequencing. Patients were clinically classified as Ohtahara syndrome (n=5), infantile spasms (n=15), Dravet syndrome (n=2), early myoclonic epileptic encephalopathy (n=1) or unclassified (n=18). None had brain malformations, metabolic abnormalities or duplications/deletions on aCGH. A first-tier analysis revealed high-effect de novo mutations in EOEE-associated genes, including STXBP1, KCNQ2, KCNT1, SCN1A, SCN2A, SCN8A, SLC35A2, and GABRA1, in 40% of cases. For patients with neonatal presentation, WES displayed a higher diagnostic yield at 9/15 (60%) (p<0.01). The two patients evolving into migrating partial epilepsy of infancy carried KCNT1 mutations. Second-tier analysis showed an excess of damaging mutations in several intolerant genes mainly related to synaptic function and brain development. WES identified de novo disease-causing mutations in 40% of patients with EOEE, showing even better diagnostic yield in cases with neonatal onset. All variants were in genes previously related to EOEE; those in STXBP1 were the most common in our cohort. Other genes and pathways enriched with de novo variants emerged as plausible candidates to produce EOEE.